A regional approach for the calculation of characteristic toxicity factors using the USEtox model; Science of The Total Environment; Vol. 655 - Belyanovskaya A. I. Alexandra Igorevna; Laratte B. Bertrand; Perry N. Nicolas; Baranovskaya N. V. Nataliya Vladimirovna (2019, 2019)
Title screen